2020
DOI: 10.1021/acs.langmuir.9b02719
|View full text |Cite
|
Sign up to set email alerts
|

Nonspherical Coacervate Shapes in an Enzyme-Driven Active System

Abstract: Coacervates are polymer-rich droplets that form through liquid−liquid phase separation in polymer solutions. Liquid−liquid phase separation and coacervation have recently been shown to play an important role in the organization of biological systems. Such systems are highly dynamic and under continuous influence of enzymatic and chemical processes. However, it is still unclear how enzymatic and chemical reactions affect the coacervation process. Here, we present and characterize a system of enzymatically activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…NPM1-rRNA condensates formed at 8°C, in either 5 mM or 10 mM Mg 2+ buffer after 60 minutes of incubation, had a striking non-spherical morphology ( Figures 2C and S4 ). The 10 mM Mg 2+ condensates appeared smaller and had lower average circularity than the 5 mM Mg 2+ condensates, but both circularities were lower than at higher temperatures, where values increased closer to 1, which is a characteristic of round liquid droplets(23). These results suggest that RNA is fully arrested at lower temperatures in 10 mM Mg 2+ , with the small gel-like condensates unable to completely fuse together.…”
Section: Resultsmentioning
confidence: 97%
“…NPM1-rRNA condensates formed at 8°C, in either 5 mM or 10 mM Mg 2+ buffer after 60 minutes of incubation, had a striking non-spherical morphology ( Figures 2C and S4 ). The 10 mM Mg 2+ condensates appeared smaller and had lower average circularity than the 5 mM Mg 2+ condensates, but both circularities were lower than at higher temperatures, where values increased closer to 1, which is a characteristic of round liquid droplets(23). These results suggest that RNA is fully arrested at lower temperatures in 10 mM Mg 2+ , with the small gel-like condensates unable to completely fuse together.…”
Section: Resultsmentioning
confidence: 97%
“…For example, the function of the LLPS-based nucleolus depends on the localization and activity of the enzyme RNA polymerase (8,10). Further, interactions of droplets with enzymatic solutes has been shown to enable triggered droplet condensation or dissolution (11,12), cargo release (12), ribozyme activity (13), transcription (14,15), and droplet shape changes (16).…”
mentioning
confidence: 99%
“…For example, Spruijt et al experimentally validated the Voorn-Overbeek model in mixtures of poly(acrylic acid) (PAA) and poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA) with different chain lengths (33). Furthermore, we recently showed that the elongation of short RNA oligomers with a template-independent RNA polymerase (polynucleotide phosphorylase) causes the onset of LLPS, and that this can be reversed by enzymatic RNA degradation (27). Finally, Saleh et al have shown that phase-separated droplets consisting of DNA nanostars can be degraded using a DNA restriction enzyme (36).…”
Section: Resultsmentioning
confidence: 99%
“…We exploit the fact that solutions of long nucleic acid polymers and positively charged polyelectrolytes can undergo liquid-liquid phase separation into a polymer-rich (''coacervate'') phase and a polymer-depleted (''solvent'') phase (23)(24)(25). LLPS increases solution turbidity because coacervate droplets scatter incoming light, so that the onset of LLPS is visible to the naked eye (26,27). By using this effect in combination with the activity of CRISPR-Cas nucleases, it is possible to robustly couple the detection of specific DNA and RNA sequences to the turbidity of a sample solution.…”
Section: Introductionmentioning
confidence: 99%